Research and Advanced Technology for Digital Libraries - David Hutchison, Takeo Kanade, Josef Kittler, Jon M. Kleinberg, Friedemann Mattern, John C. Mitchell, Moni Naor, Oscar Nierstrasz, C. Pandu Rangan, Bernhard Steffen, Madhu Sudan, Demetri Terzopoulos, Doug Tygar, Moshe Y. Vardi, Gerhard Weikum, Birte Christensen-Dalsgaard, Donatella Castelli, Bolette Ammitzbøll Jurik, Joan Lippincott. (Springer, 2017)
476p.